Associations between childhood trauma, depression, anxiety disorders and early arthritis presence - Konjikusic, Ana; Ohrndorf, Sarah; Braun, Tanja; Kluckow, Vivien; Höhne-Zimmer, Vera; Schmittat, Gabriela; Heim, Christine; Uebelhack, Ralf; Minden, Kirsten; Detert, Jacqueline; Burmester, Gerd-Rüdiger; Schaumburg, Desiree (Frontiers in Medicine, 2025)
ObjectiveTo compare the prevalence of childhood trauma, depression, and anxiety disorders between patients with early arthritis (EA) and a control group (CG). We further aimed to explore the influence of these variables on EA diagnosis.Methods and materialsThis monocentric study included 60 prospectively recruited EA patients with at least one inflammatory joint with a symptom duration of 1–12 months. The CG consisted of 60 individuals with no clinical signs of arthritis. The participants underwent a semi-structured interview screening for psychiatric disorders and completed standardized questionnaires, including the Hospital Anxiety and Depression Scale (HADS-A, HADS-D), the Childhood Trauma Questionnaire (CTQ), and the Posttraumatic Diagnostic Scale (PDS). For statistical analysis, we used SPPS© χ2 test, T-test, Mann–Whitney U-test, and binominal regression analysis.ResultsCompared to the CG, patients with EA had significantly higher rates of depression in the interview (41.7% vs. 16.7%; p = 0.03) and PTSD (13.3% vs. 3.3%; p = 0.048), and significantly higher HADS-D and CTQ childhood sexual abuse mean scores (HADS-D: 5.40 ± 4.80 vs. 3.60 ± 3.30; p = 0.047; CTQ sexual abuse: 5.91 ± 2.68 vs. 5.15 ± 1.02; p = 0.042). Binomial regression analysis revealed higher odds ratios for EA for CTQ emotional neglect (p = 0.048, OR = 1.12), CTQ sexual abuse (p = 0.040, OR = 1.4), HADS-D (p = 0.025, OR = 1.12), and lifetime depression (p = 0.040, OR = 4.00).ConclusionThe high rates of depression and PTSD in EA emphasize a potential link between psychiatric disorders and arthritis. The presence of EA might be associated with present and lifetime depressive symptoms, childhood sexual abuse and emotional neglect.